Synthesis of silver nanowires for flexible transparent electrode applications - De Guzman, Nathaniel T.; Balela, Mary Donnabelle L. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Transparent electrodes (TEs) are widely ap plied in various electronic devices such as liquid crystal displays (LCDs), light-emitting diodes (LEDs), solar cells, and touch panel displays. They are used in applications where light needs to enter and exit a device while maintaining the high conductivity. The most commonly used material for this kind of application is heavily-doped metallic oxides, mainly indium tin oxide (ITO). ITO films are highly transparent (>90 %) low sheet resistance (<10 Ω/sq). However, several drawbacks such as brittleness, high cost, and complicated fabrication process limits its applicability in flexible electronic devices. Materials that are currently being investigated to replace ITO are carbon nanotubes, graphene sheets, conducting polymers, and metal nanowires. Among these materials, networks of Ag nanowires have gained much attention due to its high conductivity and optical transparency which are comparable to ITO films. One approach to synthesize Ag nanowires is by electroless deposition (reduction) in ethylene glycol in the presence of a polyvinyl pyrrolidone (PVP). Several researches have been done to optimize the process and produce uniform and high aspect ratio Ag nanowires. Typically, highly expensive exotic seeds such as PI are used to aid in the nucleation process. This study aims to synthesize high aspect ratio Ag nanowires in controlling solution parameters, such as concentration of reagents, temperature, time, and precursor injection rate, without the aid of any exotic seeds. High aspect ratio Ag nanowires with an average length of 25 μm and diameter of 102 nm were successfully prepared by electroless deposition in hot ethylene glycol (160°C) for 1 h, using PVP (MW=55,000) to AgNO3 molar ratio of 3 at a precursor injection rate of 1ml/min . At these conditions, decahedral multiply-twinned particles (MTPs) have presumably nucleated at the initial stage of the reaction. PVP then selectively adsorbs on the {100} facets of the MTPs, preventing further deposition of Ag atoms on these sites. This leaves the {111) facets open for Ag deposition . As a result, the anisotropic growth of the MTPs is promoted. At a low PVP molecular weight (MW= 10,000) and concentration, mostly irregular particles were observed. On the other hand, relatively larger particles along with rod-like structures were present with excess PVP. This suggests that there is an optimum amount and molecular weight of PVP to promote the formation of quality Ag nanowires. Meanwhile, both high temperature and slow injection rate favor the preparation of long Ag nanowires. High temperature supplies the energy needed for the nucleation of MTPs, while low injection rate limits the number of nuclei formed at the beginning of the reaction. Consequently, more Ag atoms are available during the growth stage, which leads to long Ag nanowires. The introduction of CuCl2 on the other hand, has facilitated the formation of long nanowires with lengths of up to 50 μm even at Iow a PVP concentration. This is due to the stabilization of MTPs by Cu2+ and Cl- ions. Transparent electrodes were fabricated by spin-coating a suspension of Ag nanowires in ethanol on glass substrates. After annealing at 200°C for 1 h in air, a sheet resistance of as low as 82.24 Ω/sq at an 90.48% optical transparency (550nm) was obtained after 2 layers of coating (0. 12 mg/cm2). It was also found that both sheet resistance and optical transparency of the electrodes decreases with increasing Ag nanowires density. Flexible transparent electrodes were obtained by depositing an ink formulation containing nitrocellulose, on polymer (cellulose acetate) substrates by Meyer rod coating. The Ag nanowires have undergone a solvent washing process prior the coating process in order to remove the insulating PYP layer on their surface. A transparent electrode with sheet resistance of <100 Ω/sq at an optical transmittance of > 80% was demonstrated. Bending test showed less than 5% deviation from the mean resistance (R/Ro) after 100 cycles of bending. Moreover, the Ag nanowire films have good adhesion on the substrate due to the nitrocellulose acting as a protective layer. Lastly, a working transparent resistive touchpad sensor was built from the Ag nanowire electrodes
Thesis (M.S. Materials Science and Engineering)--University of the Philippines Diliman
Keywords: Silver; Nanowires; Nanostructured materials; Transparent electrodes